Exploring Mood and Pedagogical Implications of The Student’s Descriptive Text: A Systemic Functional Linguistic (SFL) Analysis (LPPM Universitas Buana Perjungan Karawang, 2025)
The issue in elementary school students' written communication lies in the urgent recognition of proficient writing as a critical factor for academic and personal development. Utilizing a Systemic Functional Linguistics (SFL) framework, the study investigates the mood system in descriptive text writing, particularly honing in on a 5th-grade student's work. The findings shed light on a notable gap in existing literature, emphasizing the scarcity of studies applying SFL to explore the mood system in the context of elementary school students' descriptive text writing. The research seeks to bridge this void by examining how young learners employ mood and subsequently provides valuable insights for tailored writing instruction. The methodology section outlines a qualitative approach and textual analysis, employing SFL to categorize linguistic elements to understand mood choices comprehensively. The results reveal a predominant use of the indicative mood, specifically the declarative subtype, and strategic tense variations contributing to overall coherence and temporal nuances. Understanding interpersonal grammar proves indispensable for language instruction, enriching language expression, and empowering students to articulate positions, navigate power dynamics, and construct critical responses. In conclusion, the study recommends that educators capitalize on students' inclination towards declarative statements and strategically use tenses to enhance temporal narratives, enriching language instruction in elementary schools.